2013
DOI: 10.1080/08927014.2013.796939
|View full text |Cite
|
Sign up to set email alerts
|

Coral-associated bacteria, quorum sensing disrupters, and the regulation of biofouling

Abstract: Marine biofouling, the settlement of microorganisms and macroorganisms on structures submerged in seawater, although economically detrimental, is a successful strategy for survival in hostile environments, where coordinated bacterial communities establish biofilms via the regulation of quorum sensing (QS) communication systems. The inhibition of QS activity among bacteria isolated from different coral species was investigated to gain further insight into its potency in the attenuation, or even the prevention, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 67 publications
0
39
0
1
Order By: Relevance
“…Vibrios have previously been postulated to have a role in BBD (Barneah et al, 2007;Arotsker et al, 2009), although their contribution to the initiation and progression of the disease has yet to be characterized. Although vibrios were detected at moderately low levels in both healthy coral mucus and in the black band, vibrios are readily cultivable from both sample types and have QS activity through both the AHL-based autoinducer 1 system and the furanosyl borate diester-based autoinducer 2 system (Tait et al, 2010;Alagely et al, 2011a;Golberg et al, 2011Golberg et al, , 2013Zimmer et al, 2014). In addition to AHLs and AI-2, vibrios also produce hydroxyketone CAI-1 signals (Henke and Bassler, 2004;Ng et al, 2011;Wei et al, 2012), and with this study we demonstrate that coral vibrios also produce CAI-1-like activities.…”
Section: Discussionmentioning
confidence: 99%
“…Vibrios have previously been postulated to have a role in BBD (Barneah et al, 2007;Arotsker et al, 2009), although their contribution to the initiation and progression of the disease has yet to be characterized. Although vibrios were detected at moderately low levels in both healthy coral mucus and in the black band, vibrios are readily cultivable from both sample types and have QS activity through both the AHL-based autoinducer 1 system and the furanosyl borate diester-based autoinducer 2 system (Tait et al, 2010;Alagely et al, 2011a;Golberg et al, 2011Golberg et al, , 2013Zimmer et al, 2014). In addition to AHLs and AI-2, vibrios also produce hydroxyketone CAI-1 signals (Henke and Bassler, 2004;Ng et al, 2011;Wei et al, 2012), and with this study we demonstrate that coral vibrios also produce CAI-1-like activities.…”
Section: Discussionmentioning
confidence: 99%
“…Because this bacterial biofilm formation is, in part, controlled by QS, various QSI strategies have been harnessed from marine microorganisms as compounds which could be used to interfere with bacterial QS, and thus represent novel forms of antifouling agents (Qian and Dahms, 2008; Dobretsov et al ., 2011). Among the array of marine niches, screening for antifouling compounds from coral symbiotic microbes is of particular interest because of their high biodiversity and rich secondary metabolism (Mohamed et al ., 2008; Fusetani, 2011; Karina et al ., 2013). In our present study, we found that 15% of coral‐associated bacteria exhibited inhibition activity against C. violaceum 12472.…”
Section: Discussionmentioning
confidence: 99%
“…In our present study, we found that 15% of coral‐associated bacteria exhibited inhibition activity against C. violaceum 12472. Previous studies reported that approximately 11–24% of the coral‐associated bacteria sampled were capable of QS inhibition activity against E. coli pSB1075, C. violaceum CV026 and A. tumefaciens KYC55 indicator strains (Romero et al ., 2011; Karina et al ., 2013). Our results are in line with these proportions and further suggest that coral ecosystems represent an ideal reservoir from which to develop QSI products.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations